Serological response of cattle vaccinated with a bivalent (SAT 1 and SAT 2) foot-and-mouth disease vaccine in Gaza Province, Mozambique - Vosloo, Wilna (University of Pretoria, 2013)
Dissertation (MSc)--University of Pretoria, 2012.